Cloning and sequence analysis of a partial cDNA for chicken cartilage proteoglycan core protein. - Sai, S (1986)
A chicken embryo sternal cartilage cDNA library, created in the plasmid expression vector pUC9, was screened for sequences coding for immunologically detectable core protein of the large, major proteoglycan of cartilage. A 1229-base-pair cDNA clone was isolated that contained only one extended open reading frame, which had sequences coding for a polypeptide of 379 amino acid residues. These deduced sequences corresponded to those anticipated from current models of proteoglycan structure; a deduced sequence encompassing 21 amino acids was almost identical to a known sequence of bovine nasal cartilage proteoglycan. Significant homology was found between the deduced amino acid sequence of the proteoglycan and two regions of a chicken hepatic lectin. Immunoprecipitation of the products of cell-free translation yielded a component of about 340 kDa, and transfer blot hybridization of sternal cartilage RNA showed a single mRNA of about 8.1 kilobases. Hybridizable mRNA sequences were readily detectable by dot-blot analyses of the cytoplasm of cartilaginous tissues of the chicken embryo, whereas similar analyses of prechondrogenic limb mesenchymal cells did not demonstrate such hybridizable mRNA signals.